2001
DOI: 10.1080/02652030117232
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of chromium bioavailability from the diet by an in vitro method

Abstract: An in vitro method was used to study the dialysable fraction of chromium (Cr) from the diet which simulates human gastric and intestinal digestion. The percentage of dialysed Cr was used to assess the bioavailability. The duplicate diet approach was used to obtain ten different sets of samples each representative of the normal diet consumed in southern Spain. In each case triplicate analysis of Cr was carried out by electrothermal atomization-atomic absorption spectrometry in acid-mineralized samples. The Cr d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The Cr dialysable fraction in the analysed daily meals ranged from 0•50 to 1•50 %. García et al (11) obtained similar results (0•4-1•6 %) using an in vitro method for a total dietary intake ranging from 16 to 117 mg/d. These authors reported that Cr bioaccessibility is higher for low levels of daily dietary intake (, 40 mg/d) than for levels of 40 -80 mg/d; for high levels (.…”
Section: In Vitro Chromium and Iron Dialysable Fractionmentioning
confidence: 58%
See 1 more Smart Citation
“…The Cr dialysable fraction in the analysed daily meals ranged from 0•50 to 1•50 %. García et al (11) obtained similar results (0•4-1•6 %) using an in vitro method for a total dietary intake ranging from 16 to 117 mg/d. These authors reported that Cr bioaccessibility is higher for low levels of daily dietary intake (, 40 mg/d) than for levels of 40 -80 mg/d; for high levels (.…”
Section: In Vitro Chromium and Iron Dialysable Fractionmentioning
confidence: 58%
“…The simulated gastrointestinal digestion procedure and the in vitro absorption estimation were carried out in accordance with previously reported methods (5,11) . The technique measures the Fe and Cr fraction dialysed from a sample under simulated gastrointestinal conditions and, therefore, available for absorption.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Beberapa penelitian pada tikus yang dibuat diabetes menunjukkan ekstrak labu kuning (Cucurbita moschata) memberikan efek hipoglikemik dan bertindak sebagai antidiabetes (Adams et al 2011;Chang et al 2014), ekstrak labu kuning (Cucurbita moschata) dan bubuk bijinya dapat memperbaiki sel islet pankreas dan produksi insulin (Makni et al 2010;Jin et al 2013). Menurut Glew et al (2006) minyak biji labu kuning (Cucurbita moschata) juga mengandung mineral kromium yang diketahui berperan dalam metabolisme karbohidrat, dengan penyerapan kromium terbaik <40 mcg per sajian (Garcia et al 2001).…”
Section: Junita Dkkunclassified
“…Dowling et al (1989) reported that inorganic Cr(III) was absorbed by a non-saturable passive diffusion process. In vitro studies indicate that absorption of dietary Cr from unsupplemented human diets ranges from 0.4 to 1.6 % (Garcia et al, 2001). The dialyzable Cr fraction was estimated to be about 4.6 %, this being considered an indicator of maximum Cr absorption (VelascoReynold et al, 2008).…”
Section: Absorption and Transportmentioning
confidence: 99%